REGIONAL SOCIO-ECONOMIC SYSTEMS FUNCTIONING MAIN INDICATORS ASSESSMENT IN THE ASPECT OF TERRITORY DEVELOPMENT STRATEGIES ELABORATION - SKOROBOGATA, L.; OKSENIUK, T. (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The Ukraine’s administrative-territorial structure reform, which is currently in the active phase of implementation, aims to ensure the decentralization of authority and resources in order to provide local governments with more opportunities in ensuring and improving the level of socio-economic development. But the country’s socio-economic development sustainable level is ensured, first of all, due to the evenly and sustainable development of its regions. The presence of significant disparities in regional development causes an increase in internal migration flows between the territories, contributing to the further deepening of existing problems. In this context, it is important to make programs for regional economic systems strategic development, based on comparative analysis, which will identify key issues of the region not only in comparison with the values of the studied indicators in retrospect, but also in the context of indicators of similar territories. The purpose of the study is to carry out a comparative analysis of the main indicators of the Ukraine’s regional socio-economic systems functioning. In the article carried out the comparative analysis of the main indicators of Ukraine’s regional development and identified the main trends and factors of their dynamics. Substantiated the need for comparative analysis of regional development indicators to identify existing reserves for their improvement and possible ways to use them in the strategic aspect, based on the leading experience of regional socio-economic systems.